Access to Education for Hindu Women Amidst the Patriarchal Culture of the Balinese Tribal Community on the Island of Lombok, Indonesia - Wijana, I Nyoman; Listiawati, Ni Putu; Ekaningtyas, Ni Luh Drajati (Jurnal Penelitian Agama Hindu, 2024)
This research explores and explores the low access to education for Hindu women amidst the patriarchal culture of the Balinese tribal community on the island of Lombok, Indonesia. A very strong patriarchal system limits women's roles in various aspects of life, including access to education, the economy, and participation in decision making, at important Hindu religious events. The research was conducted in West Lombok in the Balinese tribal community. The method used is a qualitative phenomenological method with observation, interview and documentation techniques for data collection. The main problem explored is how access to education for Hindu women is in the midst of a society that is very strong in its patriarchal culture. Education is identified as the main key in changing social phenomena, especially the marginalization of women's access to education in a patriarchal culture. Women who receive an education have the potential to break free from traditional limitations, build careers, and support community development. The importance of empowering women through education as an investment in sustainable development is expected to contribute to the local economy and improve family welfare. The results of this research show that resistance to social change regarding equality between men and women, especially regarding women's access to education in a patriarchal culture, is still quite strong, so that change still requires full support from the government and community organizations, as well as community leaders. This research concludes that access to education for Hindu women is still subordinate to that of men. Achieving justice and equality in access to education requires a holistic approach that involves collaboration between government, non-government organizations, and local communities, as well as community leaders. Increasing women's access to education is not only important, it is also a necessity to achieve sustainable social and economic development in advancing civilization.